Relocating the Vernacular: The Yves Beauregard Collection at the Musée national des beaux-arts du Québec - Tousignant, Zoë (Archivaria, 2008)
What is the rightful repository of vernacular photographs? Are certain institutions less suitable to the collection, preservation, and presentation of the vernacular object than others? This essay investigates these questions through the analysis of a particular photographic archive: the Musée national des beaux-arts du Québec’ s recently acquired Yves Beauregard Collection. Consisting of 3,540 vernacular photographs ranging from nineteenth-century cartes-de-visite to early-twentieth-century postcards, this collection was amassed over a twenty-year period by Québec historian Yves Beauregard. Using the writings on the notion of vernacular photography of Geoffrey Batchen as a theoretical framework and springboard, this essay proposes that these kinds of objects both destabilize and potentially enrich the art-history concepts at the foundation of the fine art museum. RÉSUMÉ Quel est le dépôt approprié pour les photographies « vernaculaires » ou du quotidien? Certaines institutions sont-elles moins convenables que d’autres pour faire l’acquisition, la conservation et la présentation de matériaux populaires? Ce texte explore ces questions en examinant une collection d’archives photographiques spécifique, la collection Yves Beauregard, qui a été acquise récemment par le Musée national des beaux-arts du Québec. Comprenant 3 540 photographies vernaculaires, à partir des cartes de visite du dix-neuvième siècle jusqu’aux cartes postales du début du vingtième siècle, cette collection a été amassée sur une période de vingt ans par l’historien québécois Yves Beauregard. En se servant de la notion de la photographie vernaculaire de Geoffrey Batchen comme cadre théorique et comme tremplin, ce texte propose que ce type d’objet remet en question et enrichit les concepts de l’histoire de l’art qui sont à la base des musées des beaux arts.